Website Quality Evaluation of PCNU Kota Depok Based on User Satisfaction using WebQual 4.0 - Huda, Khairul; Juwono, Musaid Purnomo; Nabawi, Fezan (Nusantara Journal of Artificial Intelligence and Information Systems, 2025)
This study aims to analyze the quality of the PCNU Kota Depok online news website in relation to user satisfaction. The method used is WebQual 4.0, one of the techniques for measuring website quality based on user perceptions across four dimensions: usability, information quality, interaction quality, and overall impression. The results of the study, based on Crosstab and Chi-Square tests, indicate that differences in perception across attributes in the four dimensions are not entirely influenced by respondent characteristics such as education, gender, age, and occupation. According to user perceptions, the service quality of the PCNU Kota Depok website can be measured by the highest levels of satisfaction in the following order: Overall Impression (4.09), Information Quality (3.92), Usability (3.76), and Interaction Quality (3.61). These results provide valuable insights for improving user experience and guiding future development of the PCNU Kota Depok website.